An Analytical Study on Reducing The Duration of Unscheduled Breakdowns in Scania P410 Trucks Through A Risk-Based Maintenance Strategy Using The FMEA Method at The Mining Contractor PT XYZ - Muhammad Abdullah; Fourry Handoko; Fuad Achmadi (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
High durations of unscheduled breakdowns in Scania P410 heavy truck units at PT XYZ represent a major issue affecting operational performance and unit physical availability (PA). Historical data from September 2024 to February 2025 indicate that the proportion of unscheduled breakdowns reached 72%, exceeding the company target of 40%, thus necessitating an effective, risk-based maintenance strategy. A Risk-Based Maintenance (RBM) approach integrated with Failure Mode and Effects Analysis (FMEA) was employed to identify critical components and determine improvement priorities. The analysis used the Pareto method to identify the dominant components contributing to downtime, followed by a fishbone diagram to determine root causes of failures. Risk assessment was conducted using severity, occurrence, and detection parameters to calculate the Risk Priority Number (RPN). The results indicate that suspension and brake system components are the primary contributors to unscheduled breakdowns, accounting for approximately ±40% of total downtime. Proposed improvement strategies include component modification, enhancement of the lubrication system, improvements to the electrical system, and optimization of operational parameters. Implementation of RBM based on FMEA is expected to reduce the duration of unscheduled breakdowns and improve unit reliability, thereby supporting enhanced operational performance.